Sustainable Investment: Perspectives and its impact on long-term value generation - Adriano Miñope, Diana Teresa (2024)
The sustainable investment has gained significant global relevance, driven by the implications of climate change and environmental devastation caused by excessive exploitation of non-renewable natural resources. This growing concern has motivated companies to increasingly commit to sustainability, impacting both their Corporate Social Responsibility practices and the formulation of government policies. This commitment translated into a growing demand for sustainable investments, aiming to make a positive impact on the environment and society. The primary goal of this article was to analyze the long-term impact of sustainable investments on project profitability. To achieve this, a comprehensive systematic literature review was conducted, encompassing relevant information, existing theories, previous research, and pertinent data. The results indicated that sustainable investments could have a significant positive impact. On one hand, companies committed to sustainability tended to be more profitable by reducing operational costs and increasing sales. In conclusion, the application of green finance in these investments stood out as a "win-win" strategy. Not only did it have a favorable impact on the environment, but it also had the potential to strengthen consumer loyalty. Despite these benefits, it was crucial to recognize that sustainable investments could entail higher risk, requiring careful evaluation before making investment decisions.